Safety profile of etifoxine: A French pharmacovigilance survey. (26th January 2016) - Cottin, Judith; Gouraud, Aurore; Jean‐Pastor, Marie‐Josèphe; Dautriche, Anne Disson‐; Boulay, Charlène; Geniaux, Hélène; Auffret, Marine; Bernard, Nathalie; Descotes, Jacques; Vial, Thierry
Abstract: Etifoxine chlorhydrate is a benzoxazine derivative approved for the treatment of psychosomatic manifestations of anxiety since 1979. Previously labeled adverse drug reactions (ADRs) only include drowsiness, benign cutaneous reactions, and acute hypersensitivity reactions. The objectives were to examine recent data on etifoxine‐related ADR by reviewing Individual Case Safety Reports (ICSRs) recorded in France especially unexpected ADRs. Etifoxine‐related ICSRs were extracted from the French Pharmacovigilance database from 1 January 2000 to 30 April 2012 and data from the marketing authorization holder up to 31 December 2011 were also obtained. Of the 350 cases retained for analysis, 123 (35%) were considered serious. Dermatological or acute hypersensitivity reactions were the most frequent ADRs (59%) mainly isolated cutaneous eruptions. However, there were 24 cases of severe toxidermia (DRESS in 5, erythema multiforme in 10 and Stevens–Johnson syndrome in 5) with etifoxine as the most suspected drug in 11 patients, and seven cases of vasculitis or serum sickness‐like reaction. Liver disorders were reported in 34 patients of whom 25 developed acute hepatitis with a cytolytic biological pattern in 16. Other unexpected ADRs included 16 reversible cases of metrorrhagia with positive rechallenge in 5, and three cases of biopsy‐proven microscopic colitis of which one recurred after etifoxine re‐administration. Although etifoxine has been marketed for more than 30 years, this survey identified a number of unexpected and sometimes serious ADRs, in particularly severe toxidermia and acute cytolytic hepatitis. A recent update of the French etifoxine summary of the product characteristics (SPC) was based on these findings.